AI Solutions Implementation Analysis using T-O-E Framework - Mirela-Simina MIHAI (Audit Financiar, 2023)
The author studied the impact of technological, organizational and environmental contexts on the way of implementing solutions based on Artificial Intelligence. The importance of this topic is given by the increasing interest of companies in all fields of activity in adopting solutions based on Artificial Intelligence to help achieve the desired results. The objective pursued in this research is to carry out an analysis of the current situation of financial services regarding how to implement solutions based on Artificial Intelligence, as well as a practical guide for companies that want to implement Artificial Intelligence. The Technological-Organizational-Environmental framework is a complex and comprehensive research framework for technological solutions. The technology context includes technologies in financial sector companies as well as those provided by technology companies. Organizational context refers to organizational preparation and management support in implementing such solutions. Environmental context refers to industrial characteristics and government regulations. In Romania, there are enough solutions based on Artificial Intelligence, and companies have the necessary infrastructure to implement them. The top management is interested in providing the necessary support for the implementation of solutions based on Artificial Intelligence. Legislative instability does not prevent the implementation process of Artificial Intelligence, but slows it down.